PENENTUAN LOKASI KAFE UNTUK MAHASISWA TEKNIK UNIVERSITAS MALIKUSSALEH MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING: DETERMINATION OF CAFE LOCATION FOR ENGINEERING STUDENTS OF MALIKUSSALEH UNIVERSITY USING THE SIMPLE ADDITIVE WEIGHTING METHOD - Ahmad Fajrul Amin; Munirul Ula; Fajriana Fajriana (LPPM Universitas Abdurrab, 2025)
Engineering students at Universitas Malikussaleh require a comfortable, affordable, and academically supportive space for gathering, discussion, and study. However, financial limitationsparticularly among recipients of the Kartu Indonesia Pintar (KIP) program highlight the importance of location and pricing in café selection. This study aims to determine the optimal location for a student café using the Simple Additive Weighting (SAW) method as a Decision Support System. SAW is chosen for its effectiveness in processing multi-criteria decisions by applying specific weights to each criterion. The research was conducted within the Faculty of Engineering at Universitas Malikussaleh, using primary data collected through interviews and direct observation of potential café locations. Evaluation criteria include menu prices, comfort, service quality, distance to campus, and supporting facilities. The SAW method was applied to rank the alternatives, with the highest score representing the most suitable location for students' needs. A web-based application was developed using PHP and MySQL to implement the system, and functionality was validated using both black-box and white-box testing methods. This study offers a data-driven solution for optimizing campus facilities and provides a reference model for other institutions seeking to develop inclusive and strategic student service locations.